Gambaran Diet Pada Penderita Gagal Jantung Di Poli Jantung Rsup Dr. Soeradji Tirtonegoro Klaten - Wahyuni, Tri; , Arief Wahyudi Jadmiko, S. Kep., Ns., M. Kep (2017)
DESCRIPTION OF DIET ON HEART FAILURE PATIENTS IN HEART POLY HOSPITAL DR. SOERADJI TIRTONEGORO KLATEN ABSTRACT A common cause of congestive heart failure is the damage or the reduced mass of the heart muscle due to acute or chronic ischaemia, increased vascular resistance due to hypertension, or because of tachyarrhythmias. Basically all of the conditions that cause changes in the structure or function of the left ventricle is a predisposition to congestive heart failure. Risk factors that triggered the high number of cardiovascular patients is an unhealthy diet, inactivity, smoking, and drinking alcoholic beverages for long periods of time. This study aims to overview of diet or daily diet include the type of food, size of household and weight (grams) in patients with heart failure. This study was a descriptive study. The study population was all patients with heart failure in poly RS. Soeradji Tirtonegoro Klaten in January to May 2016, amounting to 238 patients. Sample study of 110 patients obtained by purposive sampling. Collecting data using a 24-hour food recall form, while data analysis using test descriptive. Conclusion of the study is a diet or a diet daily in patients with congestive heart failure Poly Heart Hospital. Soeradji Tirtonegoro Klaten is largely non-compliant with a variety of staple food is rice, mostly eat fruit, mostly eating vegetables, and most of the tea drinking water. Keywords: diet, patients with heart failure